Artroplastia total não cimentada da articulação coxofemoral em cães - Diogo, Lúcia Izique [UNESP] (2014)
The total hip replacement is widely accepted for the treatment of severe hip dysplasia and other causes of pain or hip dysfunction in dogs. Cementless arthroplasty was developed in order to remove the durability limitations of the cemented system. The concept of this technique is based on the biological fixation. Acetabular and femoral implants are precisely fitted by pressure in a way to promote stability until the osteointegration has been completed. The success of this procedure involves the patient, the conformation of the hip joint, the precision of the implants and the quality of surgical technique. The complication rate is low, specially when it is compared to cemented procedures. Therefore, a number of considerations and care must be taken to obtain results corresponding with the high success rate of the technique. The goal of this study is to present a review of the available literature about the use of uncemented hip prosthesis in dogs. This technique is shown to be effective in the treatment of serious disorders of the canine hip with significant advantages compared to previously described methods.